Conscious sedation/monitored anesthesia care versus general anesthesia in patients undergoing transcatheter aortic valve replacement: A meta-analysis - Hung, Kuo-Chuan; Chen, Jen-Yin; Hsing, Chung-Hsi; Chu, Chin-Chen; Lin, Yao-Tsung; Pang, Yu-Li; Teng, I-Chia; Chen, I-Wen; Sun, Cheuk-Kwan (Frontiers in Cardiovascular Medicine, 2023)
Background To compare the merits and safety between conscious sedation/monitored anesthesia (CS/MAC) and general anesthesia (GA) for patients receiving transcatheter aortic valve replacement (TAVR). Measurements Databases including EMBASE, MEDLINE, and the Cochrane Library databases were searched from inception to October 2022 to identify studies investigating the impact of CS/MAC on peri-procedural and prognostic outcomes compared to those with GA. The primary outcome was the association of CS/MAC with the risk of 30-day mortality, while secondary outcomes included the risks of adverse peri-procedural (e.g., vasopressor/inotropic support) and post-procedural (e.g., stroke) outcomes. Subgroup analysis was performed based on study design [i.e., cohort vs. matched cohort/randomized controlled trials (RCTs)]. Main results Twenty-four studies (observational studies, n = 22; RCTs, n = 2) involving 141,965 patients were analyzed. Pooled results revealed lower risks of 30-day mortality [odd ratios (OR) = 0.66, p < 0.00001, 139,731 patients, certainty of evidence (COE): low], one-year mortality (OR = 0.72, p = 0.001, 4,827 patients, COE: very low), major bleeding (OR = 0.61, p = 0.01, 6,888 patients, COE: very low), acute kidney injury (OR = 0.71, p = 0.01, 7,155 patients, COE: very low), vasopressor/inotropic support (OR = 0.25, p < 0.00001, 133,438 patients, COE: very low), shorter procedure time (MD = −12.27 minutes, p = 0.0006, 17,694 patients, COE: very low), intensive care unit stay (mean difference(MD) = −7.53 h p = 0.04, 7,589 patients, COE: very low), and hospital stay [MD = −0.84 days, p < 0.00001, 19,019 patients, COE: very low) in patients receiving CS/MAC compared to those undergoing GA without significant differences in procedure success rate, risks of cardiac-vascular complications (e.g., myocardial infarction) and stroke. The pooled conversion rate was 3.1%. Results from matched cohort/RCTs suggested an association of CS/MAC use with a shorter procedural time and hospital stay, and a lower risk of vasopressor/inotropic support. Conclusion Compared with GA, our results demonstrated that the use of CS/MAC may be feasible and safe in patients receiving TAVR. However, more evidence is needed to support our findings because of our inclusion of mostly retrospective studies. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022367417.